The Online Advertising Industry: Economics, Evolution, and Privacy - Evans, David S. (The Journal of economic perspectives, 2009)
Online advertising accounts for almost 9 percent of all advertising in the United States. This share is expected to increase as more media is consumed over the Internet and as more advertisers shift spending to online technologies. The expansion of Internet-based advertising is transforming the advertising business by providing more efficient methods of matching advertisers and consumers and transforming the media business by providing a source of revenue for online media firms that competes with traditional media firms. The precipitous decline of the newspaper industry is one manifestation of the symbiotic relationship between online content and advertising. Online-advertising is provided by a series of interlocking multisided platforms that facilitate the matching of advertisers and consumers. These intermediaries increasingly make use of detailed individual data, predictive methods, and matching algorithms to create more efficient matches between consumers and advertisers. Some of their methods raise public policy issues that require balancing benefits from providing consumers more valuable advertising against the possible loss of valuable privacy.